2021
DOI: 10.3389/fped.2021.689024
|View full text |Cite
|
Sign up to set email alerts
|

The Age, Sex, and Geographical Distribution of Self-Reported Asthma Triggers on Children With Asthma in China

Abstract: Background: Asthma can be exacerbated by many triggers, and the heterogeneity of asthma triggers is clear among children with asthma. This study describes asthma triggers using a large-scale electronic dataset from the smartphone-based Chinese Children's Asthma Action Plan (CCAAP) app and aims to examine the difference in asthma triggers among different subgroups of children with asthma.Methods: Data from the smartphone-based CCAAP app between February 22, 2017, and November 23, 2020, were reviewed, and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Thirdly, in this survey, data were collected via parents-reported electronic questionnaires, which might yield risk for recall or reporting bias, although strict quality control was implemented. Additionally, items analyzed are more general, and some transient factors such as quick weather change from warm to cold and severe air pollution that were found to be susceptible to respiratory infection ( 38 , 39 ) are not collected in this survey. We agree that further incorporation of more factors is necessary to improve model precision and recall, which are relatively low, even under the optimal gNB algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, in this survey, data were collected via parents-reported electronic questionnaires, which might yield risk for recall or reporting bias, although strict quality control was implemented. Additionally, items analyzed are more general, and some transient factors such as quick weather change from warm to cold and severe air pollution that were found to be susceptible to respiratory infection ( 38 , 39 ) are not collected in this survey. We agree that further incorporation of more factors is necessary to improve model precision and recall, which are relatively low, even under the optimal gNB algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of male participants was also a factor precluding generalisability of our results, but it was also a factor limiting putative sex bias -as the lipoprotein subfraction profile is influenced by sex. Some variables were not measured in our intervention study, such as deeper biomolecular pathways that could have explained the observed changes in lipoprotein profile [63,64].…”
Section: Limitationsmentioning
confidence: 99%